Study on the prevalence and pattern of malnutrition among children under 5 years in chennai - SUNDARI.S; SHANTHI RAMESH; JAGADEEP RAMESH (International Journal of Pharma and Bio Sciences, 2017)
Malnutrition among under five children is a major public health problem. To estimate the prevalence and pattern of malnutrition among under-five children using the WHO Z- score system. This cross-sectional community-based survey was conducted among the beneficiaries of an Anganwadi centre in an urban slum of Egmore, Chennai. Background information, weight and length/ height of the children were obtained. The WHO Anthro software (version 3.2.2) was used to calculate the Z scores for underweight, stunting, wasting and overweight. A total of 357 children aged one month to 5 years were enrolled in this study. The overall prevalence of underweight, stunting and wasting was found to be 19.9% (95% CI 15.9-24.4), 17.1% (95% CI 13.3- 21.4) and 21.6% (95% CI 17.4 -26.2) respectively. The prevalence of underweight and wasting in the present study increased with increasing age (p < 0.05). The difference in the prevalence of under nutrition among male and female children was small and this difference was not found to be statistically significant (p > 0.05). The overall prevalence of overweight children was found to be 1.4%.The prevalence of under nutrition was found to be high among the urban under privileged children in Chennai. This, once again, reinforces the fact that under nutrition in children continues to be a major public health problem in our country and every effort should be taken to prevent under nutrition and its long term consequences.